2000
DOI: 10.1590/s0100-879x2000001200005
|View full text |Cite
|
Sign up to set email alerts
|

Bone mineral density in Brazilian men 50 years and older

Abstract: Bone mineral density (BMD) in the lumbar spine (LSBMD), femoral neck (FNBMD) and whole body (WBBMD) and whole body tissue composition were evaluated in 288 Brazilian men 50 years and older, 80% white and 20% Mulattoes. Age was inversely correlated with WBBMD (r = -0.20) and FNBMD (r = -0.21) but not with LSBMD (r = 0.03). Body mass index and weight showed a strong positive correlation with WBBMD (r = 0.48 and 0.54), LSBMD (r = 0.37 and 0.45) and FNBMD (r = 0.42 and 0.48). Correlation with height was positive b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
2

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 35 publications
2
8
0
2
Order By: Relevance
“…The machine normal reference range for male subjects was used to determine T-scores since Zerbini et al [20], comparing these data with the BMD of 288 Brazilian men, observed no significant differences between the Brazilian and US/European male population for BMD in the femoral neck.…”
Section: Discussionmentioning
confidence: 99%
“…The machine normal reference range for male subjects was used to determine T-scores since Zerbini et al [20], comparing these data with the BMD of 288 Brazilian men, observed no significant differences between the Brazilian and US/European male population for BMD in the femoral neck.…”
Section: Discussionmentioning
confidence: 99%
“…2 The risk of fracture is directly associated with bone mineral density (BMD). 3 Bone loss is expected with age, 4,5 and it dramatically increases the incidence of hip and vertebral fractures in both men and women. 6 The frequency of occurrence of bone fractures in South America is lower than in other regions of the world; however, it is possible that this problem is becoming intensifi ed due to the increasing life expectancy of the population on this continent.…”
Section: Introductionmentioning
confidence: 99%
“…6 In 2000, Zerbini et al published the densitometric analysis of 288 Brazilian men aged 50 years or older (mean age 62.5 years), concluding that hip BMD was similar in the population studied, compared to the North American and European, but this study did not include very elderly men (80 years old or more), or presented a percentage of men with osteoporosis, allowing the comparison of prevalences. 7 The lack of studies on the prevalence of osteoporosis in men in Brazil and the results found in this study reinforce the importance of health care policies aimed to the male population to prevent and treat osteoporosis, in order to reduce the risk of fractures. Most data from literature comes from foreign populations, and the treatment of male osteoporosis was done with bisphosphonates and teriparatide.…”
Section: Discussionmentioning
confidence: 51%